Modeling of stakeholder influence on effectiveness of team decisions in the digital network space of crisis management centres of the EMERCOM of Russia - T. V. Popov (Цифровая социология)
The article deals with issues related to modeling of stakeholder influence on effectiveness (sustainability) of teamwork in crisis management centres (hereinafter referred to as CMC) of the Ministry of the Russian Federation for Civil Defence, Emergencies and Elimination of Consequences of Natural Disasters (hereinafter referred to as EMERCOM of Russia) while analysing, forecasting development and resolving/reducing conflictness of social emergencies (hereinafter referred to as SE). The problem is considered from the perspective of using a nonlinear approach in modeling in the form of the Verhulst equation which allows to analyse complex social processes. The influence of different stakeholder groups is modeled at different values of the “a” parameter of its intensity– weak, medium, strong. The article presents the results of practical research on assessing the influence of stakeholders, primarily the external ones, on effectiveness (sustainability) of the CMC teamwork in the analysis, forecast of development, and resolution/reduction of conflictness of SE. The definition of SE is given as an attractor that has emerged due to unresolved social contradictions which have caused an imbalance in public relations. The work of the CMC teams is conducted in the digital network environment of the centres, and it introduces certain specifics into its activities. The research shows the general scheme of the stakeholder approach implementation in team management in the analysis, forecast of development and resolution/reduction of conflictness of SE. The author presents the results of the nonlinear modeling of effectiveness (sustainability) of the CMC teamwork, depending on the intensity of stakeholder influence on decisions made by the team. A system of indicators characterising the regression model of the “a” coefficient of stakeholder influence is proposed, the specific values of which can be measured during field research. Three modes (three types of attractors) of teamwork are investigated. The key objective of the study is to create prerequisites for the formation of a digital twin of the CMC teamwork of the EMERCOM of Russia in SE.